2023
DOI: 10.3390/jcm12154882
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT and SPECT/CT Imaging of HER2-Positive Breast Cancer

Abstract: HER2 (Human Epidermal Growth Factor Receptor 2)-positive breast cancer is characterized by amplification of the HER2 gene and is associated with more aggressive tumor growth, increased risk of metastasis, and poorer prognosis when compared to other subtypes of breast cancer. HER2 expression is therefore a critical tumor feature that can be used to diagnose and treat breast cancer. Moving forward, advances in HER2 in vivo imaging, involving the use of techniques such as positron emission tomography (PET) and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Moreover, a range of studies have found that the metabolic parameters derived from PET imaging could significantly differentiate the HER2 expression status in breast cancer and colorectal cancer, which also suggested that PET/MRI may be used in predicting HER2 status and guiding the antibody-drug conjugate therapy for BLCA. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a range of studies have found that the metabolic parameters derived from PET imaging could significantly differentiate the HER2 expression status in breast cancer and colorectal cancer, which also suggested that PET/MRI may be used in predicting HER2 status and guiding the antibody-drug conjugate therapy for BLCA. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%